2017
DOI: 10.3390/rs9060552
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Sentinel-1A SAR Coastal Wind Speeds Against Scanning LiDAR

Abstract: High-accuracy wind data for coastal regions is needed today, e.g., for the assessment of wind resources. Synthetic Aperture Radar (SAR) is the only satellite borne sensor that has enough resolution to resolve wind speeds closer than 10 km to shore but the Geophysical Model Functions (GMF) used for SAR wind retrieval are not fully validated here. Ground based scanning light detection and ranging (LiDAR) offer high horizontal resolution wind velocity measurements with high accuracy, also in the coastal zone. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Although this work focuses on predicting coastal winds, we are not considering the effects of the wind speed gradient present at the discontinuity between the land and the sea, which increases the uncertainty in the predictions. Studies on coastal gradients [37] have reported velocity reductions between 4% and 8% from 3 km to 1 km from the shore. Over 3 km from the coast, velocity gradients of 0.5%/km have been observed for different offshore sites [38].…”
Section: Evaluation Of Predicted Wind Speedsmentioning
confidence: 99%
“…Although this work focuses on predicting coastal winds, we are not considering the effects of the wind speed gradient present at the discontinuity between the land and the sea, which increases the uncertainty in the predictions. Studies on coastal gradients [37] have reported velocity reductions between 4% and 8% from 3 km to 1 km from the shore. Over 3 km from the coast, velocity gradients of 0.5%/km have been observed for different offshore sites [38].…”
Section: Evaluation Of Predicted Wind Speedsmentioning
confidence: 99%
“…SAR is better suited for resolving winds in coastal zones because of its higher spatial resolution (Christiansen et al, 2006). It has been shown that SAR-derived winds can accurately depict wind speed gradients measured by ground-based lidars near the coastline (Ahsbahs et al, 2017) and that SAR wind fields show similar mean wind speed variations as those experienced by wind turbines (Ahsbahs et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For these directions, coastal wind speed gradients are expected to occur, caused by the roughness change between land and sea. Coastal gradients from SAR have been shown to agree well with lidar wind speeds for the first few kilometers from shore (Ahsbahs et al, 2017).…”
Section: D) Influences Of Diurnal Variabilitymentioning
confidence: 78%